Binge drinking in 14-year-old Italian students is correlated with low or high psychological well-being: a cross-sectional study. (4th March 2021) - Gostoli, Sara; Fantini, Luana; Casadei, Sara; De Angelis, Veronica A.; Rafanelli, Chiara
Abstract: Balanced levels of Psychological Well-Being (PWB) can represent protective factors for human functioning. PWB has not been investigated among young adolescents who practice binge drinking (BD), a popular pattern of alcohol intake, defined as the consumption of five or more alcoholic units in one session. The negative impact of BD on psychophysical health has been extensively studied, but there is scarcity of studies investigating the influence of psychological variables on BD in early adolescence. The main aim of this study was to fill the gap in the literature, focusing on PWB as a new possible target of preventive interventions. One thousand six hundred and eighty-seven Italian adolescents completed questionnaires assessing BD, cannabis use, lifestyle, allostatic overload, subclinical psychological distress, problem-solving, and PWB. Binge drinkers represented 9% of the sample. Among them, 71%, 26%, and 3% binge drank monthly, weekly, and daily, respectively. Stress (higher frequency of stressful life events), psychological distress (higher hostility), and PWB dimensions (higher scores on positive relations and lower on purpose in life) were associated with BD. These new findings on unbalanced levels of PWB could represent the potential target of longitudinal studies aimed to implement specific preventive interventions among young adolescents. Implications for research and prevention are discussed.